A PETROLOGICAL, MINERALOGICAL, AND CHEMICAL ANALYSIS OF THE LUNAR MARE BASALT METEORITE LAPAZ ICEFIELD 02205, 02224, AND 02226 - Joy K.H.; Crawford I.A.; Downes H.; Russell S.S.; Kearsley A.T. (My University, 2006)
LaPaz Icefield (LAP) 02205, 02226, and 02224 are paired stones of a crystalline basaltic lunar meteorite with a low-Ti (3.21-3.43% TiO2) low-Al (9.93-10.45% Al2O3), and low-K (0.11-12% K2O) composition. They consist mainly of zoned pyroxene and plagioclase grains, with minor ilmenite, spinel, and mesostasis regions. Large, possibly xenocrystic, forsteritic olivine grains (<3% by mode) contain small trapped multiphase melt inclusions. Accessory mineral and mesostasis composition shows that the samples have experienced residual melt crystallization with silica oversaturation and late-stage liquid immiscibility. Our section of LAP 02224 has a vesicular fusion crust, implying that it was at one time located sufficiently close to the lunar surface environment to have accumulated solar-wind-implanted gases. The stones have a comparable major element composition and petrography to low-Ti, low-Al basalts collected at the Apollos 12 and 15 landing sites. However, the LAP stones also have an enriched REE bulk composition and are more ferroan (Mg numbers in the range of 31 to 35) than similar Apollo samples, suggesting that they represent members of a previously unsampled fractionated mare basalt suite that crystallized from a relatively evolved lunar melt. © The Meteoritical Society, 2006.